Il cambiamento della scuola secondo il paradigma dell’outdoor education per la rinascita della persona - Chistolini, Sandra; Villanova, Matteo (Studi sulla Formazione/Open Journal of Education, 2022)
The return to school was as traumatic for the school as being at home forced by the pandemic emergency. The inability to adapt immediately to change whether in the case of preventing contagion or in the case of resuming the rhythm of daily life abruptly thrown back into the vortex of the schedules that punctuate our existence, demonstrates the human person's need to know and master events. There is in fact a clear gap between the change brought about by norms and the internalization of the sense of change itself. The freedom in which a person's autonomy is expressed clashes with the need to accommodate what is indispensable to civil coexistence. The continuous process of adaptation to events moves toward finding that balance which, although, temporary, remains indispensable for the reorganization of the school into new forms. Among the choices of greatest interest, outdoor education presents itself as the paradigm of a desired and expected innovation capable of opening the school to the world to know how to handle emergency and everyday life.